Estrategia didáctica "JUGANDO CON BLOQUES LÓGICOS" para mejorar el aprendizaje del área lógico matemática en niñas y niños de cinco años de la I.E.I. Nº 288 "Ana Sofía Guillena Arana" del distrito de Rioja - Arévalo Gonzáles, Pilar (2009)
The present investigation has had as objective to apply the didactic strategy Playing with logical blocks to improve the level of learning of the mathematical logical area in girls and children of five years of the l.E_ Nº 288 Ana Sofia Guillena Claws of the district of Rioja; I study that is justified for their relevance in the process of teaching of the area of Logical Mathematical that is developed in the level of initial education and to have allowed to stimulate in girls and children the abilities and specific dexterities by means of the use of the logical blocks as half didactic to favor the mathematical logical knowledge. The strategy Playing with logical blocks was systematized keeping in mind the contributions of the sociocultural theory of Vygostki, the contributions of the theory cognitive of Piaget and the contributions of the theory of !he mathematical game of Zoltan Dianas. Besides other studies that served us as antecedents of the investigation. Supported before in the theoretical contributions mentioned and the antecedents of the investigation, thought about the following hypotheses: Alternative hypothesis; lf the didactic strategy is applied Playing with logical blocks', then he/she will rise the level of learning of the mathematical logical area significantly in girls and children of five year of the Educational lnstitution Nº 288 Ana Sofia Guillena Claws of the district of Rioja. Null hypothesis; lf the didactic strategy is applied Playing with logical blocks", then the level of learning of the mathematical logical area won't rise in girls and children of five year of the Educational lnstitution N" 288 Ana Sofia Guillena it Claws of the district of Rioja. The sample taken for the study was conformed by 25 girls and children of the lnitial Educational lnstitution Nº 288 Ana Sofia Guillena it Claws of the district of Rioja of the 5 year-old age who you/they conformed the experimental group. To this elected sample, as well as to a group control, he/she was administered a pre test to evaluate the level of learning of the mathematical logical area before the execution of the strategy Playing with logical blocks', subsequently and for a period of one month fourteen serial sessions of learning were developed in those that he/she put into practice the proposed strategy. After having culminated this period, the search test was administered, so much to the group control as to the experimental group to determine the effects taken place by the strategy, especially in the study sample. Once obtained the data, you proceeded to the analysis and respective interpretation of the same ones, being demonstrated that the application of the didactic strategy Playing with logical blocks elevated the level of achievement learning significantly in Beginning (I Average = 10), to Achievement in process (I Average= 15), in the three components of the mathematical logical area in girts and children of 5 years of the Educational lnstitution Nº 288 Ana Sofia Guillena Claws of the district of Rioja.